2007
DOI: 10.1111/j.1600-0501.2006.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between peri‐implant crevicular fluid volume, concentrations of crevicular inflammatory mediators, and composite IL‐1A –889 and IL‐1B +3954 genotype: A cross‐sectional study on implant recall patients with and without clinical signs of peri‐implantitis

Abstract: The Interleukin-1 polymorphism investigated exerted only little influence on the peri-implant crevicular immune response, and this influence appeared to be of limited impact in sites with established peri-implantitis lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(140 citation statements)
references
References 56 publications
2
132
2
2
Order By: Relevance
“…Varying reports have attempted to associate specific genotypes of the immune response with peri-implantitis. There is some evidence that IL-1 polymorphisms, particularly in conjunction to smoking, may confer an increased risk for peri-implant bone loss or implant loss (61,62), but this may not adequately reflect the produced levels of inflammatory mediators (63)(64)(65). Therefore, to-date no specific genotype or systemic inflammatory marker exists that can reliably indicate peri-implant disease progression or susceptibility (66).…”
Section: Pathogenesis Of Peri-implant Diseasesmentioning
confidence: 99%
“…Varying reports have attempted to associate specific genotypes of the immune response with peri-implantitis. There is some evidence that IL-1 polymorphisms, particularly in conjunction to smoking, may confer an increased risk for peri-implant bone loss or implant loss (61,62), but this may not adequately reflect the produced levels of inflammatory mediators (63)(64)(65). Therefore, to-date no specific genotype or systemic inflammatory marker exists that can reliably indicate peri-implant disease progression or susceptibility (66).…”
Section: Pathogenesis Of Peri-implant Diseasesmentioning
confidence: 99%
“…Studies have also demonstrated that single nucleotide polymorphisms (SNP) in the IL-1 gene may hold an increased risk for the development of peri-implantitis, particularly when combined with smoking (Andreiotelli et al 2008;Bormann et al 2010). However, the presence of a specific SNP does not necessarily translate into higher levels of IL-1β in PICF (Lachmann et al 2007;Jansson et al 2005;Melo et al 2012). Although there is good evidence of the involvement of IL-1β as a crucial mediator of the host inflammatory response in peri-implant tissues (Murata et al 2002;Salvi et al 2010;Ataoglu et al 2002), this needs to be complemented with further interventional studies, whereby IL-1β inhibitors are part of the treatment.…”
mentioning
confidence: 99%
“…Some studies concentrated on the issue of the relationship between this gene polymorphism and risk factors for dental implant failure (Lachmann et al 2007;Lin et al 2007;Rogers et al 2002;Shimpuku et al 2003). Rogers et al (2002) observed no association between IL-1A-889 and IL-1B?3953 alleles or the composite genotype and the failure of dental implants.…”
Section: Resultsmentioning
confidence: 99%